Variation in neutrophil levels and artemisinin-based combination therapy efficacy in West-Africa - Djimde, Moussa; Kayentao, Kassoum; Tshiongo, Japhet Kabalu; Fofana, Bakary; Arama, Charles; Sirima, Sodiomon B; Ouedraogo, Jean Bosco; Beavogui, Abdoul Habib; Sagara, Issaka; Dicko, Alassane; Mens, Petra F; Schallig, Henk DFH; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: Polymorphonuclear neutrophils (PMN) are involved in pathogen clearance by phagocytosis. However, the role of PMNs in the efficacy of artemisinin-based combination therapy (ACT) is poorly understood. Methodology: In a prospective longitudinal in vivo study, neutrophil rates were compared with malaria carriage after treatment with different ACTs: Artemether - lumefantrine (AL), Artesunate - amodiaquine (ASAQ), Dihydroartemisinin - piperaquine (DP) or Pyronaridine artesunate (PA). The study cases were classified as having neutropenia, normal neutrophil levels or neutrophilia depending on the level of neutrophils in the blood. This study included 3148 patients and was analyzed using R. Results: On day 7, only four patients in the neutropenia group and treated with AL had a malaria positive blood smear based on microscopy. On day 28, the rate of recurrent parasitemia in the AL arm was significantly higher in neutropenia patients (50.9%) than in patients with normal rates of neutrophils (43.1%) or in those with neutrophilia (6.0%) (p < 0.001). In ASAQ arm, the rate of recurrent Plasmodium falciparum parasitemia was 58.8% in the neutropenia group versus 29.4% in patients with normal rates of neutrophils and 11.8% in patients with neutrophilia (p < 0.001). No patient treated with DP with normal neutrophil counts or neutrophilia was carrying malaria parasites on day 28. Among the 15 patients with parasitemia on day 28 in the PA arm, 11 (73.33%) had neutropenia while 4 (26.67%) had a normal neutrophil count (p < 0.001). Conclusions: Patients with neutropenia had higher rates of recurrent P. falciparum parasitemia after ACT.